The Neurobiology of Reduced Autobiographical Memory Specificity. Issue 11 (November 2018) - Barry, Tom J.; Chiu, Connie P.Y.; Raes, Filip; Ricarte, Jorge; Lau, Hakwan
Abstract : There has been a recent growth in investigations into the neural mechanisms underlying the problems recalling specific autobiographical events that are a core feature of emotional disorders. In this review we provide the first synthesis of this literature, taking into account brain as well as cognitive mechanisms. We suggest that these problems are driven by idiosyncratic activation in areas of the brain associated with assigning salience and self-relevance to emotional memories. Other areas associated with inhibiting distraction and constructing vivid memory representations are also important. Each of these mechanisms may work independently or in concert with one another. Importantly, this interaction between mechanisms may differ between diagnostic and demographic groups such that similar problems in specificity may be characterised by different mechanisms. Given this challenge, neuroimaging may prove useful in identifying patient-specific biomarkers for interventions. Highlights: People with emotional disorders often have difficulty retrieving specific autobiographical memories. This difficulty is explained by problems in brain regions involved in executive functioning, emotion regulation, and the (re-)experiencing of self-relevant and emotional information. There are also differences between individuals as to which of these mechanisms explains the specific problem they experience. Neuroscientific methods offer exciting opportunities to explore unanswered questions regarding culture and age differences in memory specificity. The findings presented here offer novel suggestions for interventions which target these problems in people with emotional disorders.